Konglomerasi Walt Disney Company dan Implikasinya di Indonesia dalam Kajian Ekonomi Politik Media - Puspitaningrum, Deby; Ekowati, Sari; Priatna, Priatna; Bender, George Wilhelm (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The conglomeration of the Walt Disney Company as a global media and entertainment giant has significant impacts on the media industry in Indonesia. Through media political economy strategies such as vertical integration, horizontal integration, and specialization, Disney has established hegemony that influences local media content. This study employs qualitative methods with a critical paradigm approach to observe these implications. Findings indicate that the homogenization of content produced by Disney affects the perceptions of Indonesian society, particularly concerning definitions of beauty and gender constructions. Therefore, enforcing regulations against media ownership concentration and supporting local companies is crucial to maintaining cultural diversity and the quality of national content.